Video self-modeling and collegiate field hockey: The effect of a self-selected feedforward intervention on player hitting ability - Foltz, B. D.; Denton, L. K.; Steinfeldt, J. (Research & Investigations in Sports Medicine, 2020)
The purpose of this study is to test the effectiveness of a Video Self-Modeling (VSM) intervention on the hitting performance of collegiate field hockey players. Using a multiple-baseline single-subject design, 4 female collegiate field hockey players took part in a 3-week VSM intervention following a 1-week baseline measurement period. Each participant watched a personalized VSM video once per day on the device (e.g., computer, smartphone) of their choosing. The 1-minute videos consisted of recordings of each participant`s performances edited to show only the shots that the participant selected as ideal representations of her swing. Measurements of participant performance (e.g., shot accuracy) were taken four times per week during the 3-week intervention phase. Findings of this study may have implications for psychology practitioners in regard to the potential utility of modern technology when delivering VSM interventions. Additionally, the results may provide insight for sport psychology practitioners into the efficacy of VSM interventions with field hockey players.